Self Disclosure pada Tokoh dalam Film Ipar Adalah Maut - Liza Amalia Dewi; Nur Maghfirah Aesthetika (Yayasan Literasi Sains Indonesia, 2025)
Self disclosure is a crucial aspect of interpersonal communication that can either strengthen or undermine relationships. This study aims to analyze self disclosure in the characters of a film produced by MD Pictures and directed by Hanung Bramantyo entitled “Ipar Adalah Maut” using DeVito's theory. The research employed a qualitative method through scene observation, dialogue analysis, and documentation. The findings reveal significant differences in the amount of disclosure, a shift in valence from positive to negative, and low accuracy due to lies by Aris and Rani that damaged trust. In terms of intention, self disclosure was used both for emotional support and manipulation, while intimacy between Aris and Rani was toxic compared to the supportive closeness between Nisa and Manda. The study concludes that the quality of self disclosure determines the direction of interpersonal communication: openness without honesty and sincere intentions may turn into a manipulative tool that destroys relationships. This research contributes to communication studies by applying self disclosure theory in film analysis as a medium that reflects family dynamics.